The Story of Prophet Musa AS and the Development of Taqwa Among the Elderly: An Analysis Based on Tafsir Al-Manar - Kauthar Abd Kadir; Siti Mardhiyah Kamal Azhar; Farah Umaina Najwa Ismail (Usuli Faqih Research Centre PLT., 2026)
Indexed by MyCite